Adverse childhood experiences and living in the socially deprived areas in adulthood: a cross-sectional study of the nationwide data in Japan - Natsu Sasaki; Takahiro Tabuchi; Takeo Fujiwara; Daisuke Nishi (BMC, 2023)
Abstract Objectives This study aimed to examine whether having adverse childhood experiences (ACEs) was associated with living in a deprived area in adulthood. Methods The cross-sectional study was conducted by using nation-wide data in 2022 of the Japan COVID-19 and Society Internet Survey (JACSIS). Participants were community dwelling people 18 years or older. ACEs were assessed by Japanese version of 15-items ACE measurement tool (ACE-J). Living condition was measured by Area Deprived Index (ADI) and Densely Inhabited District (DID) based on zip code. Multivariable logistic regression to analyze the associations between ADI and ACE 4 + was conducted, controlling for individual-level factors, such as age, sex, marital status, and education, as an additional analysis. Results The total of 27,916 participants were included in the analysis. The prevalence of emotional neglect, childhood poverty, and school bullying were 38.2%, 26.5%, 20.8%, respectively. 75% of the population had one or more ACE(s). The number of ACEs was associated with significantly higher risk of living in deprived area in the adulthood (p = 0.001). ACEs were not associated with living in density area. The association between ADI and ACEs 4 + was non-significant after controlling the individual-level factors. Conclusion People with higher number of ACEs tend to live in deprived areas in adulthood. Policy makers in highly deprived areas can apply the trauma-informed approach for the community care and support, which is critical to mitigating deficit perspectives and facilitating comprehensive support for those with ACEs.